Household Food Insecurity, Mother's Feeding Practices, and the Early Childhood's Iron Status - Salarkia, Nahid (Int J Prev Med, 2015)
BACKGROUND: Health consequences of food insecurity among infants and toddlers have not been fully examined. The purpose of this study was to assess the relationship between household food insecurity, mother's infant feeding practices and iron status of 6–24 months children. METHODS: In this cross-sectional study, 423 mother-child pairs were randomly selected by multistage sampling method. Children blood samples were analyzed for hemoglobin and serum ferritin concentrations. Household food security was evaluated using a validated Household Food Insecurity Access Scale. The mother's feeding practices were evaluated using Infant and Young Child Feeding practice variables including: The duration of breastfeeding and the time of introducing of complementary feeding. RESULTS: Based on the results, of the studied households only 47.7% were food secure. Mild and moderate-severe household food insecurity was 39.5% and 12.8%, respectively. Anemia, iron deficiency (ID), and iron deficiency anemia were seen in 29.1%, 12.2%, and 4.8% of children, respectively. There was no significant association between household food insecurity; mother's feeding practices and child ID with or without anemia. CONCLUSIONS: We found no association between household food insecurity and the occurrence of anemia in the 6–24 months children. However, these findings do not rule out the possibility of other micronutrient deficiencies among the food-insecure household children.